Del palenque a la escena : antología crítica del teatro afrolatinoamericano - Cordones-Cook, Juanamaría; Jaramillo, María Mercedes, 1949-; Robledo, Ángela Inés, 1954- (Universidad Nacional de Colombia, Facultad de Ciencias Humanas, Departamento de Literatura, 2014)
An anthology of dramatic works by Afro-Hispanic authors from across Latin America.